PENGEMBANGAN MEDIA KARTU KATA DALAM PENINGKATAN KEMAMPUAN MEMBACA AWAL SISWA KELAS I UPT. SD NEGERI 064034 MEDAN JOHOR - Juliani Juliani; Hidayat Hidayat (Jurnal Inovasi Penelitian, 2023)
The background of this research is the low beginning reading ability in the Indonesian subject of Class I UPT students. SD Negeri 064034 Medan Johor Medan City for the 2020/2021 Academic Year. This is due to the dependence of students on teachers by applying conventional methods, still oriented towards results, lack of variety of methods and less attractive learning media so that students' potential is not optimally developed. As a result, students' ability to read at the beginning is very low and has an impact on low student learning outcomes. Given these conditions, it is necessary to have instructional media that can improve the early reading skills of grade I students. The purpose of this study was to improve beginning reading skills in the Indonesian language class I UPT students. SD Negeri 064034 Medan Johor City of Medan for the 2020/2021 Academic Year. The type of research used by researchers is Research & Development (R&D). Research Development or Research and Development is a method used to produce products and test the effectiveness of these products. To be able to produce certain products, research that is of a needs analysis nature is used (interview/qualitative method is used). There are two types of data sources in research, namely: primary and secondary data sources. Based on the results of the research conducted, it can be concluded that the use of word card media can improve initial reading skills in the Indonesian language subject of class I UPT SD Negeri 064034 Medan District Johor Medan City Academic Year 2020/2021.